Miasto widziane z okien dyliżansu (na podstawie itinerarium Jakuba Lanhausa z lat 1768-1769) = The city seen from windows of the stagecoach (based on Jakub Lanhaus`s "Itinerarium" from 1768-1769) - Umińska-Tytoń, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to answer the question of how a monk, who travels to Rome in the 18th century perceives and describes cities. To what extent he continues the tradition of the old Polish diaries, and to what extent he creates an individual, subjectivised picture of the cities he passes or visits.
Keywords: miasto; podróżopisarstwo; dziennik podróży; city; travel journalism; travel journal